Synthesis and Characterization of Bioactive Transition Metal Complexes of Cu(II), Co(II) and Ni(II) using DFMPM and 1,4-Diamino Butane - A. Anusha; Isac sobana Raj C.; Allen Gnana Raj G. (International Journal of Research in Chemistry and Environment (IJRCE), 2018)
Cardanol ,a naturally occurring aliphatic chain substituted phenol derived from cashewnut shell liquid (CNSL) wasused for the preparation of Schiff base ligand using 1,4 diamino butane. The Schiff base complexes of Cu(II) Co(II) and Ni(II) of diαformylmethoxybis(3pentadecenylphenyl)methane (DFMPM) and 1,4-Diamino butane were synthesized in three stages. The ligand and complexes were characterized by UV-visible,IR Spectroscopy.The elemental analysis, melting pointmolar conductance,magnetic susceptability, SEM,XRD, antibacterial, antifungal activity and DNA cleavage were also studied. The conductance measurements indicate that all the complexes of non-electrolytes. The result indicate that the complexes of Cu(II),Co(II) and Ni(II) metal ion intake indicates the ligand can be used for the removal of these metals from water . The SEM and XRD studies revealed the nano crystalline nature of the complexes.